Environmental Life Cycle Assessment of Two Types of Flexible Plastic Packaging under a Sustainable Circular Economy Approach - ÇİFTÇİOĞLU, GÖKÇEN ALEV (My University, 2024)
While it is of great importance to evaluate plastic waste within the framework of a circular economy today, it is also of great importance to evaluate flexible plastic packaging, which is increasingly used in order to prevent environmental problems. To avoid the disadvantages experienced in recycling due to its multilayer nature, in this study, a life cycle assessment was made for flexible packages consisting of PET/metallized PET/PE and PP/metallized PP/PP with the data provided by the R&D Center of Elif Plastik Ambalaj Sanayi ve Tic. A.¸S.-Huhtamaki Flexibles Istanbul. Within the scope of this evaluation, two types of flexible packaging were analyzed, and an optimal flexible packaging structure for Türkiye was revealed by comparing different scenarios based on different methods in SimaPro 8.1.1.16. LCA was performed for both packages with cumulative energy demand (CED) and CML-IA methods. Four scenarios with different amounts of recycled raw materials were compared against the existing system and a fifth scenario, where electricity is assumed to be obtained from solar energy. Overall, we found that the largest environmental impact was in the existing system. However, despite being a renewable energy source, we observed that the solar energy scenario had almost as significant an impact as the existing system. When scenarios involving recycled raw materials were examined, we clearly observed that as the amount of recycled raw materials increased, the environmental impact decreased. Therefore, it emerged that the scenario with the highest amount of recycled raw materials is the most optimal scenario in many respects. There are clear differences in the results due to differences in plastic types. This study, conducted with real data, is highly important for the flexible packaging literature. A table has been provided for changing the type of plastic, changing the source of electricity generation, and reducing waste by using recycled raw materials in order to make flexible packaging more environmentally beneficial. Keywords: circular economy; LCA; life cycle assessment; flexible packaging; environmental life cycle assessment (ELCA); SimaPro; sustainability
Keywords: Sosyal ve Beşeri Bilimler; Coğrafya; Sosyoloji; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Çevre Mühendisliği; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Bilgisayar Bilimleri; Donanım; Mühendislik ve Teknoloji; Social Sciences and Humanities; Geography; Sociology; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Environmental Engineering; Information Systems, Communication and Control Engineering; Computer Sciences; Equipment; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Sosyal Bilimler (SOC); Çevre / Ekoloji; Bilgisayar Bilimi; Mühendislik; Yerbilimleri; Sosyal Bilimler Genel; ÇEVRE BİLİMLERİ; BİLGİSAYAR BİLİMİ, DONANIM VE MİMARLIK; TELEKOMÜNİKASYON; ENERJİ VE YAKITLAR; COĞRAFYA; ÇEVRE ÇALIŞMALARI; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Social Sciences (SOC); ENVIRONMENT/ECOLOGY; COMPUTER SCIENCE; ENGINEERING; GEOSCIENCES; SOCIAL SCIENCES, GENERAL; ENVIRONMENTAL SCIENCES; COMPUTER SCIENCE, HARDWARE & ARCHITECTURE; TELECOMMUNICATIONS; ENERGY & FUELS; GEOGRAPHY; ENVIRONMENTAL STUDIES; Bilgisayar Bilimi (çeşitli); Fizik Bilimleri; Coğrafya, Planlama ve Geliştirme; Sosyal Bilimler ve Beşeri Bilimler; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Çevre Bilimi (çeşitli); Enerji Mühendisliği ve Güç Teknolojisi; Donanım ve Mimari; Bilgisayar Ağları ve İletişim; Yönetim, İzleme, Politika ve Hukuk; Computer Science (miscellaneous); Physical Sciences; Geography, Planning and Development; Social Sciences & Humanities; Renewable Energy, Sustainability and the Environment; Environmental Science (miscellaneous); Energy Engineering and Power Technology; Hardware and Architecture; Computer Networks and Communications; Management, Monitoring, Policy and Law; circular economy; environmental life cycle assessment (ELCA); flexible packaging; LCA; life cycle assessment; SimaPro; sustainability